Regularity of a crisis: media framing of the 2015 transboundary haze issue in Indonesia, Singapore, and Malaysia - Rochyadi-Reetz, Mira; Budiono, Olivia Deskarina; Wolling, Jens (Penerbit Universiti Kebangsaan Malaysia, 2020)
The problem of the haze caused by huge forest fires persists as an annual transboundary problem for Indonesia and the rest of Southeast Asia. In 2015, the problem was worse than ever before, affecting many countries in the Association of Southeast Asian Nations (ASEAN) and causing respiratory ailments for more than half a million Indonesians. This study explores the media framing of the haze problem in Indonesia from June to December 2015. Using Entman’s framing approach, it investigates how media outlets from Indonesia, Malaysia, and Singapore covered the crisis. Articles from six online media outlets published in these three countries were analysed. Using cluster analysis, this research identified three frames as follows: (1) crisis frame, (2) immediate action frame, and (3) regular problem frame. The first cluster/frame consists of articles giving high salience to all problems and causes of the forest fires provoking the haze. In contrast, the second frame mostly ignores causes and problems and focuses almost exclusively on the need for immediate action. The third frame, which represents more than 60% of the articles, covers the haze problem as a regular issue without emphasizing prominently either the different aspects of the problem itself or its causes and solutions. Further results show that the media in Singapore and Malaysia used the crisis frame more often than the media in Indonesia.